AUTOMATED DIMENSIONING OF ASSEMBLY STRUCTURES OF MACHINE TOOLS BY USING COMPENSATORS - Lengerov, Angel; Salapateva, Silviya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the results of the obtained dependencies for determination of the dimensions and the number of compensators in assembling units of machine tools. An algorithm for automated dimensioning with non-adjustable compensators has been developed.The non-adjustable compensators are parts that are pre-fabricated with different dimensions. In the assembly process, that one is used providing the set size of the initial link in the particular configuration of the constituent links. The initial conditions for dimensioning the compensator are the results of the constructive design of the assembly with CAD products. As a result of this design, the nominal dimensions of all the parts of structural consideration are determined and under the condition to achieve the nominal size of the initial link. The tolerances and limiting dimensions of the parts, excluding those of the compensator, are chosen by the designer-constructor according to the functional purpose of the parts and the technological capabilities of the methods for their manufacture. This does not require limitations of the dimensional analysis but functional and cost-effective accuracy of the parts is taken into account. Dimensioning is done by applying a series of procedures, which are discussed in detail in the paper and the number of compensators by groups is determined. Based on the applied procedures is proposed an algorithm for sizing the units of machine with non-adjustable compensators. The tolerance for manufacturing the compensators shall be symmetrical in relation to the nominal dimension. On the basis of the dependencies obtained for the dimensions and the distribution of the compensators in groups, an algorithm and software for automated dimensioning of the structures with non-adjustable compensators can be created.